2022
DOI: 10.1111/bpa.13078
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of misfolded SOD1 outlines distinct patterns of motor neuron pathology and death during disease progression in a SOD1G93A mouse model of amyotrophic lateral sclerosis

Abstract: Early misfolded superoxide dismutase 1 (mfSOD1) accumulation, motor neuron (MN) degeneration, and microgliosis are hallmark pathological features in SOD1 G93A amyotrophic lateral sclerosis (ALS) mice. Because of the different vulnerabilities of distinct MN subtypes, degenerating and surviving MNs coexist in different proportions during disease progression. By examining the expression of misfolded conformers of SOD1 using specific antibodies, we defined distinct MN phenotypes that were evaluated during disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 146 publications
0
8
0
Order By: Relevance
“…A recent study identified a necroptotic motor neuron subtype in the SOD1G93A mutant mice, which displayed the presence of large vacuoles that were positive for the exosome marker CD81 and flotillin in immunofluorescence analysis. 158 However, a direct correlation of the observed exosome-positive vacuoles as the only source of ALS is not shown; the study confirms that the degenerating MNs employ EVs to mediate neuroinflammation and disease spread in ALS. Another aspect of ALS pathology is proteinopathy, which involves the aggregation of Tdp-43 in the brain.…”
Section: Huntington's Diseasementioning
confidence: 73%
See 1 more Smart Citation
“…A recent study identified a necroptotic motor neuron subtype in the SOD1G93A mutant mice, which displayed the presence of large vacuoles that were positive for the exosome marker CD81 and flotillin in immunofluorescence analysis. 158 However, a direct correlation of the observed exosome-positive vacuoles as the only source of ALS is not shown; the study confirms that the degenerating MNs employ EVs to mediate neuroinflammation and disease spread in ALS. Another aspect of ALS pathology is proteinopathy, which involves the aggregation of Tdp-43 in the brain.…”
Section: Huntington's Diseasementioning
confidence: 73%
“…Intriguingly, the degenerating MNs can act as a potent contributor to ALS progression and pathology in the later stages of the disease. A recent study identified a necroptotic motor neuron subtype in the SOD1G93A mutant mice, which displayed the presence of large vacuoles that were positive for the exosome marker CD81 and flotillin in immunofluorescence analysis . However, a direct correlation of the observed exosome-positive vacuoles as the only source of ALS is not shown; the study confirms that the degenerating MNs employ EVs to mediate neuroinflammation and disease spread in ALS.…”
Section: Role Of Evs In Brain Disorders: Involvement In Pathogenesis ...mentioning
confidence: 99%
“…Protein misfolding is a feature of SOD1 ALS, with accumulations particularly prominent within the spinal cord in both human patients and rodent models. 41–43 Increases in misfolded proteins have also been reported in the context of denervation due to nerve ligation. 44 Thus, it is possible that the more modest structural alterations we observed in SOD1 G93A mice are a general phenomenon relating to denervation, rather than specific to ALS.…”
Section: Resultsmentioning
confidence: 94%
“…Although the relative frequency of SOD1 gradually decreased, its absolute frequency remained stable. This phenomenon may be attributed to the evolution of SOD1 research topics, from loss-of-function and oxidative stress in the beginning to prion-like transmission mechanisms in recent years ( Rotunno and Bosco, 2013 ; Silverman et al, 2016 ; Salvany et al, 2022 ). Some topics, such as excitotoxicity and apoptosis, have gradually attracted less attention.…”
Section: Discussionmentioning
confidence: 99%